Kelayakan usaha tani Hutan Kemasyarakatan (HKM) pola monokultur dan agroforestri di Desa Air Terjun Kabupaten Kerinci - Putri, Adela Salsabila; Ahyauddin, Ahyauddin; Fazriyas, Fazriyas; Nurmansah, Rahmad (ULIN: Jurnal Hutan Tropis, 2024)
The Community Forest Area (HKm) of Air Terjun Village is an area that provides direct real benefits for farmers who are located around the community forest area and has natural wealth that can be developed to provide farmers with income for the family economy. This research was conducted in Air Terjun Village, Siulak District, Kerinci Regency. This research aims to determine the feasibility of a cinnamon monoculture business and a potato, coffee and cinnamon agroforestry business from the use of areas within community forests. Data collection was carried out using structured interviews using questionnaires. Determination of respondents was carried out using the Snowball method with data analysis using cost analysis, revenue analysis, income analysis, internal analysis of return and payback period analysis. The results of the research showed that the cultivation of cinnamon monoculture planting patterns and cinnamon, coffee and potato agroforestry in Air Terjun Village, Kerinci Regency had decent/profitable results. However, the profits and return on capital are faster in agroforestry planting patterns because the agroforestry planting pattern relies on 3 types of plants, whereas the monoculture planting pattern only relies on 1 type of plant.